2021
DOI: 10.3390/nano11010199
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Characteristics of Tricalcium Aluminate in the Presence of Nano-Silica

Abstract: Tricalcium aluminate (C3A) is the most reactive component of the Portland cement and its hydration has an important impact on the workability and early strength of concrete. Recently, nanomaterials such as nano-silica (nano-SiO2) have attracted much attention in cement-based materials because of its pozzolanic reactivity and the pore-filling effect. However, its influence on the hydration of C3A needs to be well understood. In this study, the hydration kinetics of C3A mixed with different percentages of nano-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Researchers have achieved new heights in the realm of nanotechnology with the discovery of nano-particles (NP) finer than 100 nm in size [28][29][30]. NP may be used to improve the mechanical characteristics of various materials, such as polymers [31][32][33] and cementitious materials [34][35][36][37], and are also useful in the medical, engineering, and food domains [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have achieved new heights in the realm of nanotechnology with the discovery of nano-particles (NP) finer than 100 nm in size [28][29][30]. NP may be used to improve the mechanical characteristics of various materials, such as polymers [31][32][33] and cementitious materials [34][35][36][37], and are also useful in the medical, engineering, and food domains [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3b, seen from the increasing main diffraction peaks of SiO 2 , Ca(OH) 2 , CSH and Ettringite, explanations were provided to tested physical properties. The presence of SiO 2 enriched the reaction system, and the Ca(OH) 2 released in an alkaline environment reacted with SiO 2 by the volcanic ash reaction, and thus activating the steel slag through the reaction process and the dissolution to promote the dissolution of more active substances 38 . The additional CSH acted as additional nucleation sites, promoting the formation and growth of reaction products from the dissolved units 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of SiO 2 enriched the reaction system, and the Ca(OH) 2 released in an alkaline environment reacted with SiO 2 by the volcanic ash reaction, and thus activating the steel slag through the reaction process and the dissolution to promote the dissolution of more active substances. 38 The additional C S H acted as additional nucleation sites, promoting the formation and growth of reaction products from the dissolved units. 39 While SiO Al 3+ entered into the alkaline pore solution to form hydrated sulphoaluminate with better conditions, which was conducive to stabilizing the growth activity of Anorthite and improving the phase conversion.…”
Section: Crystal Phase Analysismentioning
confidence: 99%
“…This effect correlates well with the results obtained from the measurement of plastic cracking. The changes observed in compressive strength from the first day up to 28 days later indicated that hydration experienced an acceleration caused by the addition of colloidal silica [61,62]. Consequently, a final setting time was approached, thereby reducing the period of exposure to the environment on fresh concrete.…”
Section: Strength Of Shotcrete Materialsmentioning
confidence: 99%